Cost and co-morbidities associated with hypoglycemic inpatients in Belgium. (2nd January 2016) - Chevalier, P.; Vandebrouck, T.; De Keyzer, D.; Mertens, A.; Lamotte, M.
Abstract: Background and objectives: Little is known about the economic burden of hypoglycemia in Belgium, or its related co-morbidities. This study aimed at estimating the cost and length of stay associated with hypoglycemia-related hospitalizations in diabetic patients in Belgium and the association between hypoglycemia and in-hospital all-cause mortality, incidence of traumatic fractures, depression, and cardiovascular diseases (myocardial infarction or unstable angina), using retrospective data from 2011. Methods: Patient data were retrieved from the IMS Hospital Disease Database, including longitudinal (per calendar year) information on diagnoses, procedures, and drugs prescribed in ∼20% of all Belgian hospital beds. The eligible population included all adult (<19 year) diabetic (both types) patients, further split between those with/without a history of hypoglycemia-related hospitalizations. Diabetes, hypoglycemia, and co-morbidities of interest were identified based on International Classification of Diseases and Related Health Problems Version 9 (ICD-9) diagnosis codes. All costs were extrapolated to 2014 using progression in hospitalization costs since 2001. Results: A total of 43 410 diabetes-related hospitalizations were retrieved, corresponding to 30, 710 distinct patients. The average hospitalization cost was €10, 258 when hypoglycemia was documented ( n = 2625), vs €7173 in other diabetic hospitalized patients ( n = 40, 785). When controlling for age and sex, a higher mortality risk (OR = 1.59; p -value <0.001), a higher incidence of traumatic fractures (OR = 1.25; p -value = 0.009), and a higher probability of depression-related hospitalizations (OR = 1.90; p -value <0.001) were observed in hypoglycemic patients. A similar risk of cardiovascular event was observed in both groups, but hypoglycemic patients were more at risk of experiencing multiple events. Conclusion: Hospitalizations for hypoglycemia are expensive and associated with an increased risk of depression and traumatic fractures as well as increased in-hospital mortality. Interventions that can help reduce the risk of hypoglycemia, and consequently the burden on hospitals and society, without compromising glycemic control, will help to further improve diabetes management.